Crop Establishment and Nutrient Management for Dry Season (Boro) Rice in Coastal Areas. (1st November 2014) - Sarangi, Sukanta K.; Maji, Buddheswar; Singh, Sudhanshu; Sharma, Dinesh K.; Burman, Dhiman; Mandal, Subhasis; Ismail, Abdelbagi M.; Haefele, Stephan M.
Abstract : Dry season (boro) rice ( Oryza sativa L.) is an important crop in coastal areas of India, but little attention has been devoted to optimize crop and resource management for this important ecosystem. Four methods of crop establishment were tested on puddled soil: direct sowing of pre‐germinated seeds with drum seeder, transplanting 12‐ and 18‐d‐old seedlings and conventional transplanting of 25‐d‐old seedlings (farmers' practice). Three nutrient treatments were also evaluated: recommended dose of fertilizers (RDF; 120–20–0 kg N–P2 O5 –K2 O ha −1 ), RDF + Azolla (2 t ha −1 ) and RDF + 5 t ha −1 of farmyard manure (FYM). Azolla is a N‐rich freshwater fern that can be produced in ponds and ditches. Drum‐seeding increased plant height, tiller number, leaf area index, and net photosynthetic rate. Grain and straw yields (4.85 and 8.13 t ha −1, respectively) were significantly higher with drum seeding than with transplanting. Grain yield was 34, 37, and 38% higher compared with 12‐, 18‐, and 25‐d‐old transplanted seedlings, respectively. Seedling age at transplanting did not affect grain yield, but the benefit/cost ratio (BCR) (1.94) was higher with drum seeding than with transplanting. Grain and straw yields under RDF + FYM were, respectively, 24 and 21% higher than RDF, but were only 11 and 12% higher compared with RDF + Azolla treatment. Integrated management practices combining a salt‐tolerant variety (Canning 7) with drum seeding and nutrient management that include chemical and organic fertilizers could enhance the productivity of boro rice in saline coastal soils.